The Contribution of Ball Launching and Ring Entrance Angle Variables in 3 points Jump Shot in Basketball - Abd, Zahraa Adnan Hadi; Shabba, Faris Sami Yousif (Journal of Physical Education, 2021)
The research aimed at identifying the values of ball launch and ring entrance angle and relations among them as well as identifying the contribution of ball launch and angle variables in 3 point jump in basketball. The researchers hypothesized statistical relation between ball launch and entrance angle. They used the descriptive method on (10) basketball players best known for their 3 point jump shot. Each player is given (10) attempts and only attempts with a larger entrance angle in recorded. The results showed that the height of ball launch players an integral role in decreasing entrance angle as well as ball launch angle did not correlate with the entrance angle. Finally, ball launch variables have no effect or contribution on ball entrance angle.